PENERAPAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP - Firdaus, Andi Mulawakkan (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This research aims to analyze the influence of the TGT type cooperative learning model on the mathematics learning outcomes of class VIII students at SMP Muhammadiyah Limbung. This type of research is pre-experimental with a design model, namely One-Group Pretest Posttest Design. The data collection technique uses mathematics learning outcomes test data collection techniques (pretest and posttest), and documentation. The research sample was students in class VIII.1 of SMP Muhammadiyah Limbung with a total of 35 students. Based on data processing using the t-test, it was concluded that there was an influence of the TGT type cooperative model on the learning outcomes of class VIII students at SMP Muhammadiyah Limbung. The research results showed that: the effect of improving student learning outcomes after being given the TGT model was 23.3%.